Tuning the morphology of ZnO nanostructure by in doping and the associated variation in electrical and optical properties. Issue 8 (September 2015) - Awad, M.A.; Ahmed, A.M.; Khavrus, V.O.; Ibrahim, E.M.M.
Abstract: In this work, Zn100− x In x ( x =0, 1, 2.5, 5 and 7.5 at%) compounds have been initially alloyed by melting method and used as precursors to prepare different nanostructures of indium (In) doped ZnO using chemical vapor deposition (CVD). The effect of In content on the structural, morphological, optical as well as electrical properties has been studied. XRD and Raman examinations demonstrate the substitution of Zn +2 ions by In +3 ions at lower indium concentrations, while In2 O3 appears as separate phase at higher In ratios. The nanowires transform to nanoflakes then nanoflowers as the In concentration increases. With regard to the optical properties, the transparency increases with increasing In and decreases thereafter. The optical band gap values increase with In content reaching its maximum value (3.28 eV) for the sample of x =5 at%. The refractive index, extinction coefficient and Urbach tail are also affected by In doping. The electrical conductivity enhances at lower doping level due to formation of thermally activated donor levels, despite this, the phase separation and phonon scattering are factors responsible for conductivity decrease at higher In content.